HUBUNGAN FAKTOR-FAKTOR RISIKO SINDROM METABOLIK TERHADAP KEJADIAN PREDIABETES PADA REMAJA AKHIR - Naufalda Almira (2023)
Medical students, who are late adolescents have a busy class schedule. This can prevent medical students from living a healthy lifestyle thereby increasing the risk of metabolic syndrome and prediabetes. Several studies have shown an increase in the prevalence of metabolic syndrome and prediabetes in late adolescents. This study aims to determine the relationship between metabolic risk factors and the incidence of prediabetes in late adolescents. This research is a quantitative study with a cross sectional design with a sample size of 100 medical students taken using a simple random sampling method. The research instruments used were demographic data questionnaires, Global Physical Activity Questionnaire (GPAQ), 24-Hour Food Recall questionnaires, and glucometers. Fisher test results show a significant relationship between gender (p=0.044), genetics (p=0.022), central obesity (p=0.014) with the incidence of prediabetes. Nutritional status (p=0.225), physical activity (p=0.628), diet (p=0.361), and smoking (p=0.072) did not have a significant relationship with prediabetes. The results of logistic regression shows genetic (p=0.017; OR= 22.242; 95% CI 1.755 - 281.905) had the strongest influence on the incidence of prediabetes. It concluded that gender, genetic, and central obesity have an effect on the incidence of prediabetes.